(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was carried out to assess effect of gamma radiation on the acidity and vitamin C content of the Citrus macroptera (Satkora) and Citrus assamensis (Ginger lime). Irradiation with doses 0.5, 1.0, 2.0, 3.0 kGy were applied to assess the effect on the titrable acidity and vitamin C contents every one week interval for total five weeks. Both titrable acidity and vitamin C content of C. macroptera, and C. assamensis are sensitive to both gamma radiation and storage time; have decreased with increase of radiation does as well as storage time and this changes of vitamin C and titrable acidity content with gamma radiation and increasing storage period have found statistically significant. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13986 Int. J. Agril. Res. Innov. & Tech. 2 (1): 1-6, June, 2012